Fixed-Point Theorem for Nonlinear F-Contraction via w-Distance - Abdelkarim Kari; Mohamed Rossafi; El Miloudi Marhrani; Mohamed Aamri (Advances in Mathematical Physics)
The aim of this paper is to introduce a notion of ϕ,F-contraction defined on a metric space with w-distance. Moreover, fixed-point theorems are given in this framework. As an application, we prove the existence and uniqueness of a solution for the nonlinear Fredholm integral equations. Some illustrative examples are provided to advocate the usability of our results.